A TOP NIGHT: Social Protest, Masculinity and the Culture of Drinking Violence - TOMSEN, STEPHEN (The British Journal of Criminology, 1997)
Although a wide research literature suggests a regular connection between drinking, violence and social disorder, much doubt remains as to the actual nature and significance of this link. Some strong insights into this are provided by a dual consideration of the tie between masculine social identity and heavy group drinking, and the importance of issues of male honour in the social interaction that leads to much violent behaviour. But as well as this, information from the author's detailed ethnographic study of assaults in public drinking venues illuminates the subjective experience of participation in acts of disorder and violence. This is filtered through understandings of certain forms and aspects of popular leisure as entailing social protest and resistance to middle class morality. Although masculinist and frequently destructive, this violence is interpreted by many drinkers as providing a liberating and attractive sense of release, group pleasure and carnival.

Nightlife Ethnography, Violence, Policing and Security - Tomsen, Stephen; Wadds, Phillip (2016)

Sexual harassment and violence at Australian music festivals: Reporting practices and experiences of festival attendees - Fileborn, Bianca; Wadds, Phillip; Tomsen, Stephen (Australian & New Zealand Journal of Criminology, 2020)
Despite the well-documented under-reporting of sexual violence, to date, no research has considered reporting practices within the specific context of music festivals. Drawing on 16 in-depth interviews with victim-survivors, this article examines survivors’ experiences of (non)reporting sexual violence in festival settings. We argue that while some barriers to reporting are shared across contexts, others play out in context-specific ways. Our research argues that the liberal, often transgressive culture of music festivals, combined with site-specific policing practices and spatial context, creates unique impediments to reporting with particular implications in responding to, and aiming to prevent, sexual violence at music festivals.
Keywords: Bibliographie; Camille; Nettoyer

Safety, sexual harassment and assault at Australian music festivals: final report - Fileborn, Bianca; Wadds, Phillip; Tomsen, Stephen (2019)
Keywords: Camille